URGENSI SISTEM SIARAN TELEVISI BERJARINGAN - Ade Armando (Jurnal Politica, 2014)
The existence of TV broadcasting system using networking is a consequence of responsibility of broadcasting media which uses the spectrum of radio frequency. It further reveals that in the system, its main institution disseminates its broadcasting to several or many regions through its local institution, regularly, in a specific schedule. This system is developed from a democratic broadcasting principle in order to encourage participation and empowerment of local television and to guarantee the variety of its content, while simultaneously protect the rights of public to have access to the content.